A gold(i)-catalysed chemoselective three-component reaction between phenols, α-diazocarbonyl compounds and allenamides. Issue 11 (15th January 2020) - Yu, Sifan; Chen, Jinzhou; Liu, Gengxin; Lei, Jinping; Hu, Wenhao; Qiu, Huang
Abstract : A gold(i )-catalysed highly chemoselective three-component reaction of phenols, α-diazocarbonyl compounds and allenamides is presented. This transformation features mild reaction conditions, high functional group tolerance, and broad applicability. Abstract : Gold(i ) catalysts are considered to be efficient in promoting sp 2 C–H bond insertion at the para position of unprotected phenols because of the exceptionally chemical reactivity of gold-stabilized carbophilic carbocations. Herein, we present a gold(i )-catalysed three-component reaction between phenols, diazocarbonyl compounds and allenamides, affording the corresponding three-component reaction products with excellent geometric selectivity ( E : Z > 20 : 1) in moderate to high yields (up to 90%) under mild conditions. Additionally, a gram-scale transformation and diverse transformations of the resulting product show the high synthetic utility of the present three-component protocol.